Project Human Resource Management: Literature Review - Taib, Khairul Mizan bin; Sanjaya, Thrisny Regina Febrianti (Edulib, 2023)
This paper aims to define the role of project human resource management inside a company, as well as its stages and impacts. using the semantic method of literature review. Based on the study's findings, companies could maintain relationships amongst their human resources and make the greatest use of their current resources through implementing human resource management projects along with overseeing their own business activities.